Small islands in the wide open sea: The importance of non-farmed habitats under power pylons for mammals in agricultural landscape - Šálek, Martin; Riegert, Jan; Krivopalova, Aleksandra; Cukor, Jan (Agriculture, ecosystems & environment, 2023)
Current lowland agricultural landscapes are characterized by a low representation of biodiversity-rich semi-natural habitats. Even in structurally simple farmlands, the presence of in-field, non-farmed habitats may be beneficial for species persistence. Here, for the first time, we evaluated the importance of non-farmed habitats under high-voltage power line infrastructure for medium-sized mammals inhabiting the intensively-used agricultural landscape. We found the clear choice (in terms of visit frequency and use-intensity) of power pylons over adjacent farmland by individual mammalian species during the winter, with a clear preference for power pylons for dominant species (European hare, roe deer, and red fox). Similarly, our results also revealed that individual mammalian species spend more time and showed a higher share of comfort behavior (e.g., feeding, resting for herbivores, and sniffing for carnivores) under power pylons, while the species mainly passed through the adjacent farmland. Finally, analyses focusing on the effect of local and landscape characteristics on mammal use-intensity underneath power pylons have revealed significant results only for European hare. European hare’s use-intensity increased with higher shrub density under power pylons, higher distance to the field edge, and shorter distance to shrub patches. Our findings demonstrated that power line infrastructure might represent crucial in-field non-farmed habitats, offering suitable resting and foraging habitats for various mammal species in agricultural landscape. These habitats may significantly contribute to increasing the biological potential of structurally simple farmlands, which should be taken into consideration in conservation planning within agroecosystems. •We studied the mammal utilization of non-farmed habitats under power pylons.•The visit-frequency and use-intensity were higher under pylons compared to farmland.•Mammals tend to spend more time with a higher rate of comfort behavior under pylons.•Power lines pylons present an overlooked potential habitat for mammals on farmland.•This should be acknowledged in conservation planning and strategies.